1994
DOI: 10.1042/bj2980213
|View full text |Cite
|
Sign up to set email alerts
|

Partial purification of a diacylglycerol lipase from bovine aorta

Abstract: A diacylglycerol (DG) lipase has been purified from a soluble subcellular fraction of bovine aorta by (NH4)2SO4 precipitation in the presence of 5.0% (w/v) Triton X-100, followed by chromatography on DEAE-Sephacel, heparin-Sepharose and octyl-Sepharose in the presence of either CHAPS or Triton X-100 detergents. Under basal conditions, the hydrolysis of a short-chain [3H]dioctanoylglycerol ([3H]diC8) substrate was much greater than that of a long-chain 1-[1-14C]palmitoyl-2-oleoyl-sn-glycerol (1-[14C]POG) substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
(51 reference statements)
1
6
0
Order By: Relevance
“…**p < 0.01; ***p < 0.001. hydrolysis) was 544 and 504 nmol⋅h -1 ⋅mg -1 with [ 3 H]diC8 and 1-[ 14 C]POG substrate emulsions, respectively (mean of two separate experiments with duplicate assays). Thus, there is no substrate specificity for DG lipase activity in SM-3 cells determined with short-and long-chain DG substrate emulsions, consistent with previous results with permeabilized A10 cells and assays with a partially purified DG lipase from bovine aorta (Lee and Severson 1994b). …”
Section: Fig 3 Generation and Metabolism Of Pc-derived Dg [ 3 H]mysupporting
confidence: 90%
See 1 more Smart Citation
“…**p < 0.01; ***p < 0.001. hydrolysis) was 544 and 504 nmol⋅h -1 ⋅mg -1 with [ 3 H]diC8 and 1-[ 14 C]POG substrate emulsions, respectively (mean of two separate experiments with duplicate assays). Thus, there is no substrate specificity for DG lipase activity in SM-3 cells determined with short-and long-chain DG substrate emulsions, consistent with previous results with permeabilized A10 cells and assays with a partially purified DG lipase from bovine aorta (Lee and Severson 1994b). …”
Section: Fig 3 Generation and Metabolism Of Pc-derived Dg [ 3 H]mysupporting
confidence: 90%
“…Therefore, the relative rates of sn-1 and sn-2 hydrolysis in DG differ between SM-3 cells (sn-2 > sn-1), A10 cells (sn-2 = sn-1) and freshly isolated cells from rabbit aorta (sn-2 < sn-1). Lee and Severson (1994b) could not detect MG lipase activity in a partially purified DG lipase preparation from bovine aorta, suggesting that separate enzymes hydrolyze the sn-1 position of 1,2-DG and the sn-2 position of the 2-MG intermediate in the lipase pathway. Nevertheless, hydrolysis through a DG and MG lipase pathway is a consistent feature for DG metabolism in cultured cell lines (SM-3 and A10 cells) that differ with respect to differentiated characteristics and in noncultured freshly isolated aortic smooth muscle cells, which presumably closely resemble functional smooth muscle cells in blood vessels, supporting the use of cultured smooth muscle cells as model systems for signal transduction research.…”
Section: Fig 5 Effect Of Thl On Dg Metabolism [ 3 H]myristate-labementioning
confidence: 59%
“…Several attempts have been made to purify soluble DG lipase from bovine aorta (17,18); however, it has not yet cloned. The enzymatic properties of DG lipases from rat brain (this study) and bovine aorta are quite similar in terms of the dependence of their enzyme activity on pH, their K m values and the effects of an inhibitor (THL) on them.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether other DG lipases are involved in the modulation of neurotransmission. DG lipase activity in bovine aorta was observed in the soluble fraction, but not in the membrane fraction (17,18), which indicated that the activity was not derived from DGL or DGL . Attempts have been made to purify the soluble DG lipase, but it has not yet cloned.…”
mentioning
confidence: 92%
“…Investigators have examined the purification of lamb pre-gastric lipase [36], of dog gastric lipase [37], of diacylglycerol lipase from bovine aorta [38], of intestinal acid lipase from rat [39], purification and characterization of bovine pancreatic lipase [40], purification and characterization of rat phospholipase [41], and the purification of lipoprotein lipase from different rat tissues [42]. An important conclusion is that lipases from different tissues subjected to identical purification steps are purified to the same extent.…”
Section: Purification Stepmentioning
confidence: 99%